Mubtada’ and Khabar in Al-Kawākib ad-Durriyyah and Syarḥ Alfiyah Ibn ‘Aqīl: A Comparative Syntactic Analysis - Lestari, Robby Jundi; Nurdian, Irwan; Derysmono, Derysmono; Nurrasyid, Hadi (Al-Fakkaar, 2026)
The study of mubtada’ (subject/topic) and khabar (predicate/comment) in Arabic grammar reveals diverse definitions and complex rules that often confuse learners, particularly in al-Kawākib al-Durriyyah and Syarḥ Ibn ‘Aqīl, which differ in their schools of thought and systematic organization. This study aims to compare the concepts of mubtada’ and khabar in both works using a qualitative library-based approach with a comparative–interpretative method and content analysis conducted through data collection, classification, and interpretation. The findings reveal significant differences in aspects related to ‘āmil, the number of musawwighāt, and the rules of taqdīm wa ta’khīr, while both works share similarities in discussing the ruling on the multiplicity of khabar, despite differing in the conditions for its annulment. These differences reflect systematic efforts and simplification strategies aligned with the characteristics and levels of each work, thereby facilitating a clearer understanding of classical Arabic grammatical concepts for modern learners